2017
DOI: 10.1016/j.jacc.2017.02.060
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Factors From Childhood and Midlife Cognitive Performance

Abstract: Cumulative burden of cardiovascular risk factors from childhood/adolescence associate with worse midlife cognitive performance independent of adulthood exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
81
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 42 publications
5
81
0
6
Order By: Relevance
“…The representativeness of the study population participating in the study was examined by comparing the baseline differences between participants and nonparticipants (Supplementary Table 1). Participants were a little younger and more often female than nonparticipants, which is common among longterm observational studies (25). Similar race and studied CVRFs were observed.…”
Section: Resultsmentioning
confidence: 52%
“…The representativeness of the study population participating in the study was examined by comparing the baseline differences between participants and nonparticipants (Supplementary Table 1). Participants were a little younger and more often female than nonparticipants, which is common among longterm observational studies (25). Similar race and studied CVRFs were observed.…”
Section: Resultsmentioning
confidence: 52%
“…Accumulation of CVD risk factors in childhood influences both arterial stiffness/thickness and cognitive function in young adulthood [1012]. Our findings demonstrate that associations between large artery stiffness and cerebral hemodynamic pulsatility manifest at a young age.…”
Section: Discussionmentioning
confidence: 67%
“…Epidemiologic studies have reported the several risk factors for this category of diseases. In the pathophysiology of atherosclerosis, impaired plasma levels of lipoproteins including high cholesterol, high LDL cholesterol, high serum TG, low HDL cholesterol, and lipid metabolism disorders are more than other factors affecting atherosclerosis [3]. Also, increased inflammation and oxidative stress are considered to be major risk factors for atherosclerosis and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%